2019
DOI: 10.28945/4275
|View full text |Cite
|
Sign up to set email alerts
|

‘A Source of Sanity’: The Role of Social Support for Doctoral Candidates’ Belonging and Becoming

Abstract: Aim/Purpose: This paper investigates the role of social support in the PhD. Despite universities’ efforts to provide a collegial PhD experience, candidates report isolation and loneliness in doctoral education – a factor contributing to attrition. Background: Previous research (Mantai & Dowling, 2015) defined social support in four categories: moral, emotional, guiding and mentoring, companionship, and collegiality. Social support is facilitated in various formal and informal groupings. Socialisation into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…Possessing academic and research skills is necessary, but no longer sufficient, to make a good supervisor. Developing and maintaining a healthy student-supervisor relationship on the other hand, has become viewed as an increasingly essential part of the supervision process (Howells et al, 2017;Mantai, 2019;Vereijken et al, 2018), and a major determinant of student success (Roach et al, 2019). Developing and facilitating such a relationship however, presents challenges to students and supervisors alike.…”
Section: Introductionmentioning
confidence: 99%
“…Possessing academic and research skills is necessary, but no longer sufficient, to make a good supervisor. Developing and maintaining a healthy student-supervisor relationship on the other hand, has become viewed as an increasingly essential part of the supervision process (Howells et al, 2017;Mantai, 2019;Vereijken et al, 2018), and a major determinant of student success (Roach et al, 2019). Developing and facilitating such a relationship however, presents challenges to students and supervisors alike.…”
Section: Introductionmentioning
confidence: 99%
“…Participants in this study shared the importance of non-specific moral support and encouragement, and while these are nebulous concepts, ‘understanding of similar experiences provides appreciation and solidarity’ that allows doctoral candidates to continue along their journey ‘at a level they otherwise (might) not believe possible’ (Wilson & Cutri, 2019, p. 59). Because the TBP doctoral journey is potentially hazardous for doctoral students’ well-being (Lovitts, 2001), institutions have an obligation to ensure that candidates have access to personal support, which should ideally complement knowledge and skill development (Mantai, 2019). While supervisors play an important role in supporting doctoral students, as a relatively new addition to the doctoral education landscape, many supervisors would not have completed their own doctoral training through this mode.…”
Section: Discussionmentioning
confidence: 99%
“…Some students are negatively impacted by the stress and pressure of doctoral research and its heavy workloads (Metcalfe, 2006). Others struggle with isolation and an inability to feel a sense of belonging in the academic community (Ali & Kohun, 2007; Mantai, 2019). Central to the doctoral experience is the relationship between the candidate and their supervisor/s, largely recognised as one of the most important factors in positive outcomes for doctoral students (Wao & Onwuegbuzie, 2011; Zhao et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Sense of belonging is, in some ways, the integration of oneself among the social contexts. While there has been a significant study of the impact of sense of belonging on undergraduate students of Color, there is increasing attention to the ways belonging impacts doctoral student success (Herzig, 2006;Mantai, 2019;O'Meara et al, 2017;Ong et al, 2018Winkle-Wagner et al, 2010. Winkle- Wagner et al (2010) found that the sense of belonging of doctoral students of Color was related to the level of support they experienced from faculty and institutional culture.…”
Section: Sense Of Belongingmentioning
confidence: 99%